Esterase‐Activatable and Glutathione‐Responsive Triptolide Nano‐Prodrug for the Eradication of Pancreatic Cancer. Issue 11 (2nd August 2021) - Sui, Binglin; Cheng, Chen; Shi, Shanshan; Wang, Mingming; Xu, Peisheng
Abstract : Triptolide (TPL) is a small molecule isolated from a traditional Chinese herb Tripterygium wilfordii Hook F and shows excellent anticancer effect for pancreatic cancer cells. However, the poor water solubility ad severe liver toxicity of TPL hindered its clinical application. Herein, TPL is covalently conjugated to a polymer and entrapped inside the core of the TPL nanogel (nTPL) to protect it from premature leakage during blood circulation. With the help of lactobionic acid (LBA), nTPL‐LBA could selectively target the tumors in an orthotopic pancreatic cancer mouse model. TPL could be subsequently released intracellularly in its original form due to the presence of elevated intracellular esterase and GSH, and eventually kills cancer cells. nTPL‐LBA treatment reduces tumor burden by 99% while not introducing TPL‐associated liver and kidney toxicities. Most importantly, more than half of the nTPL‐LBA‐treated animals are tumor‐free, suggesting that nTPL‐LBA is an effective approach in eradicating pancreatic cancer. Abstract : Triptolide (TPL) nano‐prodrug, which is responsive to triggers of glutathione and esterase, can intracellularly release a highly potent TPL. With the help of LBA targeting ligand, nTPL‐LBA effectively eradicates tumors in an orthotopic pancreatic cancer mouse model while not causing TPL‐associated systemic toxicity.